The BULT Method for Pediatric Minilaparoscopic Pyeloplasty in Infants: Technique and Results - Ludwikowski, Barbara Magda; Botländer, Michael; González, Ricardo (Frontiers in Pediatrics, 2016)
We reviewed retrospectively the results of transperitoneal minilaparoscopic pyeloplasty in children younger than 2 years. The surgical technique utilized as well as the retrograde placement of the stent is described in detail. Twenty-four consecutive children with a mean age of 7,9 months (range 1-23), a mean weight of 7.4 kg (range 4-12) and a mean follow-up 18 months (range 3-59) are included. Preoperative grade of dilatation was 3.8 (SFU scale) and postoperatively improved to 1.5. The AP diameter of the pelvis decreased from a mean of 28 mm to 9 mm. In 83% of cases there was complete resolution of hydronephrosis (grade 0-2) and the rest showed improvement. There was 1 conversion to open surgery in a child with a horseshoe kidney. There was one omental hernia though a port site in a child in whom an inappropriate drain was used. There were no stent related complications and no reinterventions for persistent or recurrent obstruction. Given these outcomes, low complication rate and excellent cosmetic results, we recommend transperitoneal MLP with a double J stent and a perirenal drain for infants requiring pyeloplasty.